2009
DOI: 10.1161/strokeaha.108.538629
|View full text |Cite
|
Sign up to set email alerts
|

Trends for Blood Pressure and Its Contribution to Stroke Incidence in the Middle-Aged Japanese Population

Abstract: Background and Purpose-Hypertension is a major risk factor for stroke. However, a substantial decrease in blood pressure levels in Japanese during the past 3 decades may have reduced contributions of hypertension to risk of stroke. The population attributable fraction, the percentage of outcomes attributable to exposure, of blood pressure for the incidence of stroke was investigated during 3 survey periods between 1963 and 1994 by means of a population-based cohort study. Methods-We explored 3 cohort data of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 29 publications
4
89
0
1
Order By: Relevance
“…26 Moreover, our findings suggested that stroke risk of subjects with prehypertension in their 50s, but not for such subjects in their 40s, was similar to that of normotensive subjects. Recent studies about relationship between elevated BP and PAF for stroke incidence of Japanese in the Japan Public Health Centre study 27 and the Circulatory Risk in Communities Study 28 suggested that the 29 Those controversial issues regarding prehypertension impact on stroke events could be because of white coat hypertension and the potential impact of fluctuations in BP levels after midlife that may affect stroke incidence. Further analysis of the relation between BP fluctuation and stroke could shed light on the issue whether early BP control over normal levels at midlife could be beneficial for prevention of stroke incidence.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, our findings suggested that stroke risk of subjects with prehypertension in their 50s, but not for such subjects in their 40s, was similar to that of normotensive subjects. Recent studies about relationship between elevated BP and PAF for stroke incidence of Japanese in the Japan Public Health Centre study 27 and the Circulatory Risk in Communities Study 28 suggested that the 29 Those controversial issues regarding prehypertension impact on stroke events could be because of white coat hypertension and the potential impact of fluctuations in BP levels after midlife that may affect stroke incidence. Further analysis of the relation between BP fluctuation and stroke could shed light on the issue whether early BP control over normal levels at midlife could be beneficial for prevention of stroke incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The Circulatory Risk in Communities Study (CIRCS) is a prospective community-based study that has been launched to prevent stroke in five communities across Japan since 1963, described in detail elsewhere 6,13,14) . Annual cardiovascular risk surveys and monitoring of cardiovascular events are systematically conducted by a research team of the Osaka Medical Center for Health Science and Promotion, the Osaka University and the University of Tsukuba.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Increased BP is the most likely precipitator of CVD and stroke. 5,7,8 Furthermore, the prevalence of glucose intolerance and obesity has increased greatly in recent years. 9,10 Diabetes mellitus (DM) has become a major public health problem 11,12 as well as a risk factor for all-cause mortality 11 and CVD.…”
Section: Introductionmentioning
confidence: 99%